Axiomatic design applied to the development of a system for monitoring and teleoperation of a cnc machine through the internet - Oliveira, Luiz Eduardo Santos de (2016)
Peer-review under responsibility of the scientifi c committee of The 10th International Conference on Axiomatic Design.